Optical investigation of mesopause using OH meinel band and OI 557.7 nm nightglow at low latitude station, Kolhapur, India - Parihar, Navin (Indian Institute of Geomagnetism, Mumbai, 2009)
Short summary : The radio signals are affected by space weather. The ionosphere imposes the most detrimental effects on the radio signal passing through it. Dispersive nature of the ionosphere and use of two frequencies in GPS facilitate estimation of ionospheric TEC which is an important parameter in the study of L-Band communication though the ionosphere. Rate of TEC (ROT) from GPS can illustrate the features of the ionospheric scintillations. Highly disturbed ionosphere can cause cycle slips in GPS data. Very good correlation is found between the TEC derived from IRI-95 model and GPS using developed software. It is concluded from the present analysis that our TEC estimation procedure may underestimate actual TEC by less than 10 TECU. The magnitude of underestimation mainly depends on the plasmaspheric electron content. It should be noted that these errors are mainly caused by the two assumptions; one is the thin-shell model assumption and the other is the homogeneity of vertical TEC in the area covered with a GPS receiver It is also evident from the results that the IRI model derived TEC values are higher than GPS TEC values in the order of few TECUs, which could be due to longer propagation path of GPS signals in the ionosphere. The satellite trajectory can give sufficient information about ionospheric conditions in space and time precisely. The GPS TEC determination software presented in this chapter can be used to process other stations data, which would be useful in mapping the distribution of ionospheric TEC over low latitude region such as India.
A thesis submitted to the University of Mumbai for the Ph.D.(Science) degree in physics under the guidance of Prof. G.K. Mukherjee.
Keywords: Optical investigation; low latitude station; OH meinel band; Kolhapur; PhD Thesis